An active PAH-degrading microbial consortium developed from dioxin-contaminated sediments via enrichment technique - Hanh, Nguyen Thi; Minh, Nguyen Hong; Hop, Duong Van; Hang, Dinh Thuy (VNU Journal of Science: Natural Sciences and Technology; Vol 25 No 3, 2009)
Abstract